Phase I and II metabolism and MRP2-mediated export of bosentan in a MDCKII-OATP1B1-CYP3A4-UGT1A1-MRP2 quadruple-transfected cell line - König, Jörg; Fahrmayr, Christina; Auge, Daniel; Mieth, Maren; Fromm, Martin; et al. (British Journal of Pharmacology, 2013)
Hepatic uptake (e.g. by OATP1B1), phase I and II metabolism (e.g. by CYP3A4, UGT1A1) and subsequent biliary excretion (e.g. by MRP2) are key determinants for the pharmacokinetics of numerous drugs. However, stably transfected cell models for the simultaneous investigation of transport and phase I and II metabolism of drugs are lacking. A newly established quadruple-transfected MDCKII-OATP1B1-CYP3A4-UGT1A1-MRP2 cell line was used to investigate metabolism and transcellular transport of the endothelin receptor antagonist bosentan. Intracellular accumulation of bosentan equivalents (i.e. parent compound and metabolites) was significantly lower in all cell lines expressing MRP2 compared to cell lines lacking this transporter (P < 0.001). Accordingly, considerably higher amounts of bosentan equivalents were detectable in the apical compartments of cell lines with MRP2 expression (P < 0.001). HPLC and LC-MS measurements revealed that mainly unchanged bosentan accumulated in intracellular and apical compartments. Furthermore, the phase I metabolites Ro 48-5033 and Ro 47-8634 were detected intracellularly in cell lines expressing CYP3A4. Additionally, a direct glucuronide of bosentan could be identified intracellularly in cell lines expressing UGT1A1 and in the apical compartments of cell lines expressing UGT1A1 and MRP2. These in vitro data indicate that bosentan is a substrate of UGT1A1. Moreover, the efflux transporter MRP2 mediates export of bosentan and most likely also of bosentan glucuronide in the cell system. Taken together, cell lines simultaneously expressing transport proteins and metabolizing enzymes represent additional useful tools for the investigation of the interplay of transport and metabolism of drugs. BACKGROUND AND PURPOSE EXPERIMENTAL APPROACH KEY RESULTS CONCLUSIONS AND IMPLICATIONS